Analysis of Vehicles Dynamic Properties from the Point of View of Passenger Comfort - Tomas Lack; Juraj Gerlici (Communications - Scientific letters of the University of Zilina, 2008)
The passenger ride comfort can be assessed via the indexes of comfort i.e. via the indirect method in accordance with the European standard ENV 12299: 1999 or 2006. This method is based on the values of accelerations knowledge in the analysed places of vehicle body. The signal of accelerations is filtered and weighted with functions that take into account the sensitivity of human body to the vehicle body vibrations in reference directions. The signal is statistically assessed and the ride comfort indexes for floor, sitting or standing positions are evaluated. The accelerations coming into the assessment of ride comfort indexes can be obtained from measurements or as results of a computer simulation. The paper deals with the accelerations analysis and their influence on the final comfort index.